Investigating the Knowledge and Attitudes towards Plastic Pollution among the Youth in Nairobi, Kenya - Nicholas Oguge (MDPI AG, 2021)
Kenya has made many attempts to regulate the production of single-use plastics through partial bans and the imposition of hefty taxes. Whereas government initiatives are crucial to resolving single-use plastic pollution, commitments made by youths can be an important part of the solution. Yet, youths are habituated to using single-use plastics without understanding fully their negative impacts. Understanding the knowledge and attitudes of youths is of the utmost importance in the effort to turn the tide against plastic pollution. This study set out to investigate knowledge and attitudes towards single-use plastics among youths in Nairobi, Kenya. This was a mixed study approach, where both qualitative and quantitative data were derived. The results showed that youths perceive single-use plastics as a serious environmental and health issue. Most respondents expressed willingness to switch to reusable alternatives if provided with financial incentives. In addition, the results showed stronger support for enhanced awareness campaigns and plastic recycling infrastructure. Social media was the most preferred channel to disseminate plastic pollution messaging among the youth. These findings are important in policy development for intensifying awareness and targeting a range of communication and financial support to reduce single-use plastic pollution.